Dose-dependent effect of romifidine on intraocular pressure in clinically healthy buffalo (Bubalus bubalis). Issue 12 (December 2019) - Rizk, A.; Nocera, I.; Briganti, A.; Abouelnasr, K.; El-Khodery, S.; Tagawa, M.; Bonelli, F.
Abstract: In the present study, changes in intraocular pressure (IOP) associated with romifidine sedation in buffalo were evaluated. Eighteen healthy adult, non-pregnant, buffalo without ocular abnormalities were used in a prospective randomized trial. Buffalo were allocated into three groups (six each). Buffalo in the treated groups received an intramuscular injection (IM) of romifidine at 40 or 50 μg/kg. The control group was administrated an equivalent volume of sterile saline (0.9% NaCl; 0.4 m l /100 kg). Baseline IOP (T0) values were obtained using applanation tonometry. Immediately afterwards, romifidine was administered and IOP values of both eyes were measured at 5, 15, 30, 45, 60, 90, 120, and 180 min post-administration. The pre-administration values (T0) of IOP for both the left and right eyes ranged from 30-36 (mean, 33 ± 1.5) mmHg and 30–35 (mean, 33.7 ± 1.4), respectively. IOP values decreased significantly after administration of both doses of romifidine compared with the placebo (P < 0.01). Compared with the control, the IOP decreased significantly in animals treated with both doses from 5-90 min post-administration in both eyes (P < 0.05). In the right eye, the lowest IOP value in the romifidine treated groups was observed at T30 (21.6 ± 1.0 and 23.3 ± 1.4 mmHg), respectively. In the left eye, the lowest IOP was observed at T60 (22.5 ± 3.0 and 23.3 ± 2.8 mmHg), respectively. In conclusion, romifidine could be recommended as an alternative analgesic in buffalo, especially for ocular affections associated with increased IOP. A dose of 40 μg/kg could be used at a low cost. Abstract : Veterinary medicine; Ophthalmology; Ruminant; Applanation tonometry; Buffalo; Intraocular pressure; Romifidine